Managing Students' Anxiety in English Language Learning: An Analysis of Teachers' Strategies - Hikmah, Pramesti Chayatul; Kholis, Adhan (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
The present research aimed to investigate the causes of students' anxiousness, the methods used by teachers to control their students' anxiety while they were learning English, and the success of the methods used at MA Raden Fatah Prambanan, Sleman. The study used a case study methodology paired with a qualitative approach. Questionnaires, classroom observations, and in-depth interviews with an English teacher were used to collect data. Most of MA Raden Fatah Prambanan, Sleman's students have basic English skills. They lack motivation and think that learning English is difficult. 85,7% of students in grade 11 experienced anxiety during English language learning, and 14,3% did not feel anxiety. To reduce student anxiety, the teacher used various teaching strategies. These strategies included implementing different learning methods, such as group discussions, reading aloud, presentations, and ice-breaking activities; using a feedback model for students; and providing motivation and encouragement to boost students' confidence. These approaches helped make a more comfortable and encouraging educational situation. Strategies that were applied consistently and appropriately helped create a more conducive learning environment and supported the development of students’ language skills. The research was expected to provide insights for teachers in managing student anxiety and serve as a reference for developing more effective teaching strategies.